Ilaj Bit Ta'leeq in Chronic Pelvic Inflammatory Disease - Shiffa, M.S.M.; Fahamiya, N.; Nageeb, B.M.; Manuha, M.I. (Faculty of Indigenous Medicine, University of Colombo, 2016)
The Unani System of Medicine is based on the concept of equilibrium and balance of natural body humours (blood, bile, black bile and phlegm). The imbalance in the quality and quantity of these humours leads to diseases ...
Keywords: Hirudo therapy; gyneacological disorders; biological substances; anti-inflammatory